2013
DOI: 10.3109/13685538.2013.826186
|View full text |Cite
|
Sign up to set email alerts
|

Living status in patients over 85 years of age after TUVRP

Abstract: Surgical risk in patients over 85 years of age was higher than patients less than the age of 80 years. A safety TUVRP could improve their voiding function and activities of daily living.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, increasing age itself is an important risk factor for postoperative morbidity and mortality (11) . The most important factor affecting perioperative morbidity and mortality in elderly patients are concomitant diseases originating from organs and systems, especially cardiovascular, pulmonary, endocrine, and neurological systems (12,13) .…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing age itself is an important risk factor for postoperative morbidity and mortality (11) . The most important factor affecting perioperative morbidity and mortality in elderly patients are concomitant diseases originating from organs and systems, especially cardiovascular, pulmonary, endocrine, and neurological systems (12,13) .…”
Section: Discussionmentioning
confidence: 99%
“…for Hol-TUIP [ 28 ]. The postoperative IPSS was 11.2 for TUVRP [ 29 ], 10.2 for HoLAP [ 28 ], and 6.5 for Hol-TUIP [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, the postoperative QoL from one selected study was 1.1 for TUVRP [ 29 ], 1.0 for HoLAP, and 1.7 for Hol-TUIP [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that nearly 60% of patients undergoing RS experience at least one complication within 90 days of surgery [16,17]. In addition, there are several studies showing the effect of aging on urological surgeries in the literature [18][19][20]. In a study comparing two age groups (75-84 years vs. !85 years) undergoing RS, Compoj et al [10] found no significant difference in the complication, 30-day mortality, and overall and cancer-specific survival rates between the groups, while the 90-day mortality rate was significantly higher in the patients aged !85 years.…”
Section: Discussionmentioning
confidence: 99%